KELIMPAHAN DAN SEBARAN LONGITUDINAL IKAN-IKAN DI SUNGAI CIDANAU, BANTEN: (Suatu telaahan khusus tentang koeksistensi ikan endemik dan ikan asing) [Species Abundance and Longitudinal Distribution of Stream Fishes in Cidanau River, Banten (with special reference to coexistant of endemic and exotic species)] - Andi Abdurahim; Sunarya Wargasasmita; Ismu S. Soewelo (Jurnal Iktiologi Indonesia, 2004)
The distribution and relative abundance of fishes were surveyed in Cidanau stream, Banten, from Cagar Alam Rawa Danau to Curug Betung. From 8 sampling stations were found 8 species. Two of eight species are endemic species and introduced species to West Java i.e Rasbora aprotaenia and Liposarcus pardalis. Special analyses and discussion about the coexistant of endemic and exotic species were carried out.